Curriculum Management During The Covid-19 Emergency - Arini, Putri Dwi; Matin, Matin; Zulaikha, Siti (Journal of Education Research and Evaluation, 2021)
The purpose of this study was to analyze distance learning activities through curriculum management for the Covid-19 emergency period. The research method used a descriptive qualitative approach at SMAN 1 Baturetno Wonogiri, Central Java and the research subjects were the principal, teachers, and several students who were taken based on the appointment. Data collection techniques through observation, interviews and documentation. The findings from the study show that the curriculum management system during the Covid-19 emergency has been running as it should, curriculum planning involving local officials and school authorities, organizing by disseminating curriculum programs to all teachers, implementing online PJJ is constrained due to school conditions and limited technology owned by students and this is a factor that makes online learning not effectively implemented, and curriculum evaluation is based on input from the school and does not involve students and parents of students.